2021
DOI: 10.1002/pts.2578
|View full text |Cite
|
Sign up to set email alerts
|

Humidity effect in heating and cooling of press‐formed paperboard food packages: Comparison of storing and heating conditions

Abstract: Press‐formed paperboard food packages were heated and cooled to study the humidity effect on the packages with a series of dimension measurements. The empty packages in the form of trays were pre‐dried or preconditioned before their packing with oatmeal, and heating humidity of the packages was altered to find the optimal storing and heating conditions for improving the dimensional stability of the trays. The dimension measurement results showed aggravated dimensional stability of the trays during the heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…4). Consistent with a previous study (Niini et al 2020b), drying the empty trays resulted in a decreased tray width due to the shrinkage of paperboard fibres during the drying process. The recorded initial tray width (165 mm) for the dried tray samples and the width of the reference tray (171 mm) were notably larger in comparison to the standard width of a GN1/4 tray (162 mm).…”
Section: Fig 2 Impact Of Tray Flange Distortion On Tray Widthsupporting
confidence: 90%
See 2 more Smart Citations
“…4). Consistent with a previous study (Niini et al 2020b), drying the empty trays resulted in a decreased tray width due to the shrinkage of paperboard fibres during the drying process. The recorded initial tray width (165 mm) for the dried tray samples and the width of the reference tray (171 mm) were notably larger in comparison to the standard width of a GN1/4 tray (162 mm).…”
Section: Fig 2 Impact Of Tray Flange Distortion On Tray Widthsupporting
confidence: 90%
“…In previous studies, the effects of the press-forming parameters and humidity conditions on the durability of press-formed paperboard trays used in food processing showed material curling and stiffness degradation as the primary negative outcomes (Niini et al 2020a,b). A lower moisture content in paperboard trays, achieved by drying the trays before food processing, was shown to improve the tray durability, as moisture absorption during the food processing was connected to the emergence of hygroscopic strains in the paperboard fibres due to hygroexpansion (Niini et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curl, as defined by Salmen, 37 is a specific type of dimensional instability which occurs when the paper material is deformed over its elastic limit. According to Niini et al, 38 this phenomenon has been also seen in press‐formed products, and it is primarily due to hygroexpansion, stress relaxation and creep of materials while absorbing or desorbing moisture in different humidity conditions. In this study, in spite of having stored all the samples in the same condition, samples made of Paperboard 1 exhibited curling during storage.…”
Section: Resultsmentioning
confidence: 92%
“…According to Niini et al, 38 showed that the thermoformed trays studied did not leak regardless of their type of coating (PE or PET) and the conditions under which they were formed. This can generally verify that the thermoforming process does not cause pinholes to appear in the coating layer of the materials.…”
Section: Damage Mechanismsmentioning
confidence: 99%